The AI-Driven Revolution: Wearable ECG Devices for Proactive Atrial Fibrillation Detection and Management - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Wearable ECG Devices, Atrial Fibrillation Detection, AI in Digital Health, AF Management, Smartwatch ECG The Silent Epidemic and the Digital Solution At...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care